ENGLISH TEACHING STRATEGIES TO STUDENTS IN AN INCLUSIVE SCHOOL - Mahisa, Refka Darmayanthi Putri; Rezeki, Yanti Sri; Surmiyati, Surmiyati (LPPM IKIP PGRI Pontianak, 2023)
This research aimed to investigate the teacher strategies in teaching English to children with special needs in Zonakata Inclusive School, Pontianak, Indonesia. This research was designed as qualitative case-study research. This design was chosen to help the researcher gain deep information about the phenomenon discussed and to explore the case intensively based on the real-life context. The research participants were two teachers in Zonakata Inclusive School who teach English to children with special needs in grade three. To get the data, observation, interview, and document review were used. The data collected was then analysed using thematic analysis. This study showed that the teachers used co-teaching and differentiated teaching strategies with the help of visual media to teach English to children with special needs. In conclusion, the participants' combination of those strategies was proven to be implemented and encouraged to be used to teach English to children with special needs.